The Increase of White Pulp Diameter of Rat Spleen After CIDR1alpha-PfEMP1 Recombinant Protein Injection - Risma Aulia Magdalena; Rosita Dewi; Irawan Fajar Kusuma; Sheilla Rachmania; Erma Sulistyaningsih (Biology, Medicine, & Natural Product Chemistry, 2026)
Exploring new protein targets for malaria vaccine development is essential in supporting malaria control strategies. One such candidate is the cysteine-rich interdomain region of Plasmodium falciparum Erythrocyte Membrane Protein-1 (CIDR1alpha-PfEMP1). The spleen, as a lymphoid organ, plays a critical role in immune responses, where activation is indicated by increased white pulp diameter. This study aimed to evaluate the immune response in rats following CIDR1alpha-PfEMP1 recombinant protein injection by measuring the spleen’s white pulp diameter. Twelve male rats were divided into two groups: a control group receiving 0.9% NaCl and a treatment group receiving 150 microgramof CIDR1alpha-PfEMP1 protein. The recombinant protein was administered subcutaneously on days 0, 21, and 42. On day 56, the rats were euthanized, and their spleens were collected, processed, and stained with hematoxylin-eosin (HE). White pulp diameters were measured microscopically (100×) using ImageJ software. The mean white pulp diameter was 22.590±3.986 micrometer in the control group and 36.607±6.739 ?m in the treatment group. Statistical analysis using the independent t-test showed a significant difference (p = 0.003). These results suggest that CIDR1alpha-PfEMP1 recombinant protein stimulates immune activity, as indicated by increased white pulp diameter in rat spleens.